In search of a music for the Sesquicentennial. The National Symphony Orchestra of Peru and the spreading (1970-1976) of a new repertoire related to the Peruvian Emancipation - Roncagliolo Bonicelli, Luis José (2023)
By proposing the concept of “second independence”, the peruvian military government of 1968 found in the celebrations for the Sesquicentennial of National Independence an important vehicle for the deployment of an ambitious plan with political, social, and cultural objectives.This work presents how this context produced and hosted a group of musical works that addressed the theme of Emancipation, from the early anti-colonial resistance to the Ayacucho Campaign, most of which were premiered or performed by the National Symphony Orchestra.It also addresses how this orchestra included music of the viceroyal epoch in this period, which responded to a surge in the performance of such music in the country, and which occurred paradoxically in these years of vehement commemoration of the emancipatory process. Thus, not only did the orchestra’s repertoire expand to two opposite historical extremes (music before Independence, and modernist and avant-garde music), but this same expansion also occurred in terms of the imaginary to which the works appeal. As a result, the orchestra’s repertoire for the first time was able to make an evocative journey through all the general stages of Peruvian history.